Effects of different packaging materials on the quality and safety of kalamay-hati during storage. - Villaruz, Ella Marie Escare
The study investigated the effects of different packaging materials on the quality and safety of kalamay-hati stored at different storage temperature conditions of chilling temperature and room temperature at different storage periods of 3 days and 7 days. Initially a survey was conducted to know the different types of packaging materials used for kalamay-hati. The survey showed that the different packaging materials mostly used in packing kalamay-hati in San Jose, Antique were banana leaf, plastic film (LDPE), and plastic container (PP). After the survey, kalamay-hati was bought from an identified producer. After microbial and physico-chemical tests were done on the product, it was divided into lots and packaged using banana leaf, LDPE and PP. After 3 days, the samples were subjected to Total Plate Count (TPC), and physico-chemical tests which include moisture (% MC) determination, aw, pH, and tests for free fatty acids value (% FFA). After 7 days of storage samples were subjected to the same microbial and physico-chemical analyses. Results on two-way ANOVA (p < 0.05) revealed that storage temperature significantly affects pH, % FFA and TPC of kalamay-hati, and storage time significantly affects pH and % FFA of kalamay-hati. The results also showed that packaging material significantly affects % FFA of the sample at two different storage temperatures, and moisture content of the sample at different periods of storage. The results also showed that there is an interaction between packaging material and storage temperature which significantly affects the pH, and % FFA of the sample. There is also an interaction between packaging material and time which significantly affects the microbial load of the sample. The study proved that the main cause of deterioration of kalamay-hati is rancidity attributed to deterioration of oil as coconut oil is one of kalamay-hati major ingredients. It is recommended that at room temperature storage, it is best to package kalamay-hati using PP and LDPE, and when stored at chilling temperature, kalamay-hati can be packaged using banana leaf.